A comprehensive review of recent approaches and Hardware-Software technologies for digitalisation and intellectualisation of Open-Field crop Production: Ukrainian case study in the global context - Laktionov, Ivan; Diachenko, Grygorii; Kashtan, Vita; Vizniuk, Artem; Gorev, Vyacheslav; Khabarlak, Kostiantyn; Shedlovska, Yana (Computers and electronics in agriculture, 2024)
•Characteristics and applications of up-to-date information technologies in open-field crop production.•Multi-criteria analysis of scientific and applied achievements in the implementation of information-oriented approach in the agriculture.•Objective substantiation of the problems in the field of agricultural digitalisation.•Localisation of approaches to the development of comprehensive soil and climatic agricultural monitoring systems.•Substantiation of perspective directions of the software and hardware of open-field crop production. Today, open-field crop agriculture is becoming an increasingly knowledge-intensive industry, driven by global trends in scientific and technological development in the digitalisation and intellectualisation of production processes. This, in turn, has a positive impact on the formation of national economies and food security in many countries, including Ukraine. The aim of this manuscript is to analyse and generalise modern approaches, as well as global and Ukrainian achievements in the field of development and implementation of comprehensive solutions for software and hardware of intelligent technologies for online monitoring of the soil and climatic conditions of agricultural production with decision support. This can be used to substantiate scientific and applied provisions for the rational utilisation of areas and resources, as well as to increase the stress resistance of crops during the full cycle of their cultivation. The object of research is non-stationary processes of aggregation, network exchange, and intelligent interpretation of distributed measurement data on the soil and climatic conditions of open-field crop enterprises. The subject of the study is methods, computer models, and means for intelligent monitoring of the soil and climatic conditions of agrotechnical facilities of open-field crop production. The important scientific and applied issue of multi-criteria analysis and logical generalisation of global and domestic trends in the field of intellectualisation and digitalisation of agricultural enterprises in open-field crop production has been solved in this manuscript. Worldwide experience in the development and implementation of technologies for the digitalisation and intellectualisation of agrotechnical processes has been analysed and summarised in the article according to the following criteria: the functional purpose of the developments, the structural and algorithmic organisation of the technologies used, the technical and functional effect obtained, the methods and approaches used for the creation of the technologies. This study enabled to identify and substantiate promising areas for the development and implementation of comprehensive hardware and software solutions for agroclimatic monitoring.